TWO CASES WITH AN IMPORTANT REMINDER. Issue 10 (9th September 2014) - Ali, Khalid; Lowman, Andrea; Powell, Rob
Abstract : Neurological presentations of HIV are common, they can mimic other neurological conditions. We describe two patients presented neurologically, the delay in recognising HIV led to clinical deterioration and unnecessary investigations. A 45-year-old woman, presented with right hemiparesis, initial assessment suggested cerebrovascular event. 5 weeks later, she represented with coma and seizures. MRI brain showed large ring enhancing lesion with multiple peripheral lesions, this was thought to represent metastaic disease. Brain biopsy revealed toxoplasmosis, HIV test was positive. She was treated with antiretroviral and anti-toxoplasmosis therapy. She was left with significant neurological impairment. A 47-year-old man, with 6-week history of gait disturbance. On examination, he was irritable, with right 6th and 7th cranial nerve palsies, right hemiparesis, dysartharia with severe peripheral and truncal ataxia. MRI scan at 2 and 6 weeks showed evolving right cerebellar peduncle lesion. HIV test was positive, JC virus PCR was positive in the CSF. A diagnosis of PML was made. He was treated with HAART, he had some immunological and neurological recovery. High level of suspicion and HIV test should be considered in all unusual neurological presentations.